The feasibility and safety of combining atrial septal defect/patent foramen ovale and left atrial appendage closure: A systematic review and meta-analysis - Song, Yi; Xing, Hang; Koch, Peter David; Li, Xiaofei; Zhang, Yan (Frontiers in Cardiovascular Medicine, 2023)
Introduction Atrial Septal Defect/Patent Foramen Ovale (ASD/PFO) occlusion is performed to prevent paradoxical embolism and reduce the risk of recurrent ischemic stroke. Left atrial appendage (LAA) closure is used as an alternative to medical therapy of non-valvular atrial fibrillation for prevention of stroke. Multiple studies have examined performing LAA and ASD/PFO occlusion. However, the feasibility and safety of combined occlusion of the left atrial appendage and ASD/PFO are not clear, furthermore, these studies are limited by their small sample sizes and retrospective analysis. In this study, we aimed to systematically review and meta-analyze the feasibility and safety of combining left atrial appendage and ASD/PFO closure. Methods PubMed, Web of Science, CNKI, Cochrane Library, Embase, and WanFang database were searched up to April 2022 to identify peer-reviewed human studies on assessing the feasibility, safety, and efficacy of combining left atrial appendage and ASD/PFO closure. The primary outcome was calculated: procedural feasibility outcome and procedural safety outcome. Results A total of 10 articles, including 340 patients from multiple countries, were included in the analysis. The principal findings of our study are: compared with single LAA closure, (i) combining PFO/ASD occlusion and LAA closure had similar procedural success proportion (98.43%, 95% CI: 96.67–100.00%), (ii) similar safety event incidences developed (1.67%, 95% CI: 0.24–3.92%), subgroup analyzed safety event incidences in death was 0.00 (95% CI: 0.00–0.33%), cardiac tamponade was 0.87% (95% CI: 0.00–2.77%), device embolization was 0.00 (95% CI: 0.00–0.60%), major bleeding was 0.00 (95% CI: 0.00–0.33%), stroke was 0.00 (95% CI: 0.00–0.02%). Conclusion Although this systematic review and meta-analysis demonstrate the technical feasibility and safety of combining closure of PFO/ASD and LAA, further studies of sufficient sample size, long-term follow-up, and rigor endpoint criteria are yet needed to fully evaluate this combination procedure for its role in clinical outcomes.